2016
DOI: 10.17146/jair.2015.11.1.2700
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Flow and Surface Water Interactions Quantification in Gunung Kidul Karst Area Using Hydro- Chemical and Stable Isotopes Data Variations

Abstract: Subsurface flow is one of the available water sources in the Karsts area such as in GunungKidul. The study of the pattern of the variations of stable isotopes content as a function oftime and its interaction with other water sources such as rain waters, groundwater, riverwater will be a very good tool to assess the potential of the subsurface flow as a water source.For this purpose, the variations of stable isotopes content of subsurface flow around GunungKidul Karsts area and its interactions with other local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Hydrochemical contents of collected samples are very important parameters to trace back the geological formation that water has passed through due to the fact that water is a good solvent [10]. and oxygen-18 ratio ( 18 O), respectively and is given in equations 1 and 2 [12].…”
Section: Stable Isotopes and Hydrochemistrymentioning
confidence: 99%
“…Hydrochemical contents of collected samples are very important parameters to trace back the geological formation that water has passed through due to the fact that water is a good solvent [10]. and oxygen-18 ratio ( 18 O), respectively and is given in equations 1 and 2 [12].…”
Section: Stable Isotopes and Hydrochemistrymentioning
confidence: 99%
“…Kebutuhan terhadap air semakin lama semakin meningkat seiring pertumbuhan penduduk dan perkembangan industri [1,2]. Karena kondisi geologi, tidak semua daerah memiliki ketersediaan air yang cukup untuk memenuhi kebutuhan masyarakat di sekitarnya, seperti yang terjadi di daerah Gunungkidul yang umumnya didominasi oleh batuan gamping [3]. Untuk memenuhi kebutuhan air, penduduk biasanya banyak memanfaatkan air yang berasal dari mata air yang muncul di beberapa lokasi.…”
Section: Pendahuluanunclassified
“…A tracer (possibly, Sulforhodamine B) injected in Sawah Ombo Pond was expected to emerge in the Bribin Underground River; instead, it appeared in Beton Spring and caused the water in Beton Dam to turn red. Subsequent hydrogeochemical studies using natural isotope and injection of an artificial tracer (uranine), e.g., Sidauruk et al [10,11], found that Sawah Ombo Pond was connected to Sriti Spring. Sidauruk et al [11] mentioned that the spring is a leak of the underground river system from Sawah Ombo Pond to Beton Spring.…”
Section: Introductionmentioning
confidence: 99%
“…However, it ignored the existence of Jomblangan Cave, which the Faculty of Forestry UGM [2] claimed was connected to Sawah Ombo Pond, and Seropan Ponor, which is the headwater of Sriti Spring (unknown lower course). Also, based on the natural isotope analysis, Sidauruk et al [10] explained that Sawah Ombo Pond does not issue water to the Bribin Underground River even though no artificial tracer test was performed in this section. Later, Setiawan et al [12] corroborate the findings of Sidauruk et al [10] through natural isotope analysis.…”
Section: Introductionmentioning
confidence: 99%